Learning Media Development based Animation on Material Jump Far Class 6 Using Adobe Animate - Saputra, Ridwan Adi; Kristina, Putri Cicilia; Junaidi, Ilham Arvan (Journal of Social Work and Science Education, 2023)
The Study this done with objective for create and produce something product form media learning based animation material jump Far For class VI. Study R&D This use model development Addie which consists from five stage, that is. 1) stage analysis, 2) stage planning, 3) stage development, 4) stage implementation and 5) evaluation. Subject on study This is student class VI elementary school 169 OKU. Technique collection data form interview no structured, questionnaire, test and documentation. Analysis data in study this is analysis validity, practicality and effect potential. this research produces a product valid animation-based learning media to use with mark 89.4% who have evaluated by three experts in category “very valid”. Based on test one-to-one yielded a value of 89.1 % with answers student category “very practical”, and based on the small grub trial the value was obtained “very practical” with value 85.2%. Besides that, media learning based animation which developed own potential effect which showed with average results study student which reach KKM 70 which set school. So that development instructional media-based animation for material jump far school base proven valid and practical as well as have a potential effect.